2010
DOI: 10.3892/ijmm_00000526
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-dependent induction of dendrite formation by ginsenoside Rh2 in cultured melanoma cells

Abstract: Abstract. Herbal remedies containing root extracts of Panax ginseng are commonly used for complementary or alternative therapies. Ginsenosides, the major components of root extracts, are responsible for ginseng's pharmacological and biological effects; however, their mechanisms of action are unclear. We examined whether membrane cholesterol was involved in the mechanism of action of ginsenoside Rh2 in cultured cells. In B16 melanoma cells, Rh2 (18.5 μM) induced dendrite formation within 2 h. Depletion of chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Reduction of cholesterol mass or cholesterol partition coefficient causes the opposite effects in membranes (Tsamaloukas et al, 2005; Zidovetzki and Levitan, 2007). In agreement with this, we observed that induction of cholesterol depletion by membrane cholesterol extraction with Mβ CD provokes the expected reduction of fluorescence anisotropy and membrane order (Gidwani et al, 2001; Zidovetzki and Levitan, 2007; Jiang et al, 2010). Interestingly, the magnitude of the change in Δ r 38°C is considerably larger in WT animals than in APP/PS1 animals, which is consistent with the greater amount of cholesterol in lipid rafts from WT animals (Fabelo et al, 2012b).…”
Section: Discussionsupporting
confidence: 81%
“…Reduction of cholesterol mass or cholesterol partition coefficient causes the opposite effects in membranes (Tsamaloukas et al, 2005; Zidovetzki and Levitan, 2007). In agreement with this, we observed that induction of cholesterol depletion by membrane cholesterol extraction with Mβ CD provokes the expected reduction of fluorescence anisotropy and membrane order (Gidwani et al, 2001; Zidovetzki and Levitan, 2007; Jiang et al, 2010). Interestingly, the magnitude of the change in Δ r 38°C is considerably larger in WT animals than in APP/PS1 animals, which is consistent with the greater amount of cholesterol in lipid rafts from WT animals (Fabelo et al, 2012b).…”
Section: Discussionsupporting
confidence: 81%
“…As the chemical structure of Rh2 is similar to the synthetic glucocorticoid dexamethasone, it is speculated that Rh2 might bind with glucocorticoid receptor (GR) or its analogous nuclear receptor and stimulate translocation of GR [ 8 ]. Rh2 has also been shown to affect cellular functions via changing the physical properties of cholesterol-regulated membrane lipid bilayers [ 26 ] or binding the lipid portion of the cell membrane [ 27 ]. Examining whether STXBP5-AS1 is responsive to glucocorticoid would provide insight into the hormone-like regulation of STXBP5-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence anisotropy of DPH and TMA-DPH B16 melanoma cells Induces dendrite formation in melanoma cells (Jiang et al, 2010) Increases membrane fluidity (Yi et al, 2009) Compacts the hydrophobic membrane core…”
Section: Rh2mentioning
confidence: 99%
“…Insertion into the lipid bilayer reduces the mobility of phosphatidylcholine. In melanoma cells, Rh2 decreases membrane fluidity as determined by diphenylhexatriene (DPH) fluorescence anisotropy; however, no change in fluorescence is observed with trimethylammonium diphenylhexatriene (TMA-DPH), suggesting that only the inner hydrophobic core is affected (Ota et al, 1987;Jiang et al, 2010). Ginsenoside Rg3 increases the fluorescence anisotropy of DPH and TMA-DPH in multidrug-resistant KB V20 cells but not in the parental KB cell, indicating a selective effect on cancer cell membranes (Kwon et al, 2008).…”
Section: Effect On Dynamic Membrane Propertiesmentioning
confidence: 99%
See 1 more Smart Citation